Salvator Rosa and Giosuè Carducci: an edition history (Prassi Ecdotiche della Modernità Letteraria, 2020)
This paper focuses on the edition of Salvator Rosa’s Satire, odi e lettere, edited by Giosuè Carducci for the «Collezione Diamante» of Gaspero Barbèra (1860). In addition to the meaning of this edition, nourished by pedagogical and civil purposes, are examined the ecdotic issues faced by Carducci, who used the Satire’s editions of 1719 and 1784, and his commentary on the texts, which starts from the comparison with the previous exegetical work by Anton Maria Salvini.
Keywords: Giosuè Carducci; Salvator Rosa; Satire; Collezione Diamante; printed editions; commentary